Adaptive Output Tracking Control for Nonlinear Systems with Failed Actuators and Aircraft Flight System Applications. (21st May 2015) - Hou, Chuanjing; Hu, Lisheng; Zhang, Yingwei
Abstract : An adaptive failure compensation scheme using output feedback is proposed for a class of nonlinear systems with nonlinearities depending on the unmeasured states of systems. Adaptive high-gain K-filters are presented to suppress the nonlinearities while the proposed backstepping adaptive high-gain controller guarantees the stability of the closed-loop system and small tracking errors. Simulation results verify that the adaptive failure compensation scheme is effective.